Aerodynamics of a short intake in crosswind - Boscagli, Luca; Christie, Robert; MacManus, David G.; Piovesan, Tommaso (Elsevier, 2022)
The next generation of turbofan aero-engines are likely to have an increase in fan diameter to reduce the specific thrust and increase the overall propulsive efficiency. More compact nacelles with possibly shorter intakes may be used to reduce weight and drag and achieve a net reduction of fuel consumption. For these compact nacelles a key consideration is the design of the short intake at the off-design conditions such as crosswind and high incidence operations. The close coupled interaction between a short intake and the fan at these off-design conditions is one of the key challenges. Previous work focused on the impact of short intake aerodynamics on the fan but there is a similar requirement to understand the impact of the fan on the viable short intake design space. This paper addresses the influence of the fan on the separation onset of the flow within a short intake under crosswind conditions. The effect of the fan on the separation characteristics of the intake boundary layer was considered both from a steady and an unsteady point of view. A hierarchy of fan computational models was used to separately assess the different aerodynamic contributions and to evaluate a net effect of the fan on the intake critical condition. Steady computational fluid dynamics analyses showed a notable positive effect of the fan on total pressure loss at post-separation conditions relative to a configuration without the fan. However, unsteady analyses revealed that fan unsteadiness has an adverse impact on the intake separation characteristics which reduces the intake critical conditions by about 15%. The main mechanisms behind the unsteady interaction were identified. Overall this work addresses, for the first time, the role of fan unsteadiness on the separation characteristics of the boundary layer within a short intake in crosswind.
Keywords: Short intake; CFD; Crosswind; Unsteady; Turbofan